The Journey of Honorary Teacher to Become Permanent Teacher - Uswatun Hasanah; Syamsul Arifin; Nur Kholis Malik; Encep Syarifudin; Deni Iriyadi (Journal of Educational Sciences, 2026)
This article examines the life journey of an honorary teacher toward permanent teacher status using a narrative life-story research approach. This journey is understood as a transformative process involving not only administrative changes but also social, professional, psychological, and spiritual identity changes. This research shows that the dynamics of honorary teachers' lives, from initial idealism, social pressure, uncertainty about the future, the struggle to participate in the PPPK selection process, to finally receiving formal status as a permanent teacher, form a complex and gradual identity construction. The fifteen core paragraphs in this article are structured using the PREC format, with each paragraph using a unique reference as required. The results show that honorary status is often associated with structural injustice, low welfare, career uncertainty, and consistent psychological burdens. However, through long struggles, honorary teachers develop personal resilience, professional commitment, and spiritual meaning in their service. The transition to permanent teachers not only increases economic security but also strengthens social dignity, expands responsibilities, and forms a more stable professional identity. This study emphasizes that status change is not merely an administrative event, but an existential journey that reflects the dignity of the teaching profession.